Psychobiography: Ragil Kencono Discovers and Overcomes His Subpersonality and His Family Subpersonalities - Dewi, Nabila Rahma; Nurazizah, Firly; Syakirah, Dzikra Rahma; Novianti, Riska; Puspitarini, Hesti; Salbina, Tyas; Zahra, Azizah; Haryani, Sri; Rohani, Alia; Prabowo, Hendro (Psychosophia: Journal of Psychology, Religion, and Humanity, 2025)
Psychobiography of Ragil Kencono, a 28-year-old man, has embarked on an emotionally and spiritually transformative journey. He has dedicated himself to the exploration of transpersonal psychology, guided by mentors who have continuously supported his path. Through this process, he has identified and integrated multiple subpersonalities within himself. Following his studies in transpersonal psychotherapy and participation in workshops on letting go, mindfulness, and compassion, Ragil not only uncovered his own subpersonalities, but also successfully addressed sibling rivalry with his older brother, assisted his father in achieving greater self-understanding, and facilitated the resolution of one of his mother’s subpersonalities. This biographical study aims to provide a detailed account of Ragil Kencono’s journey in recognizing and integrating his subpersonalities. The research employs in-depth interviews with probing techniques, generating a comprehensive and chronological narrative of his life experiences from childhood to the present. The findings indicate that Ragil successfully identified and integrated his subpersonalities, as well as those of his family, through a structured four-stage process: recognition, acceptance, inclusion, and synthesis.